SUN-037 Diagnosis Challenge in Type 4 Familial Partial Lipodystrophic Syndrome - Vantyghem, Marie-Christine (J Endocr Soc, 2019)
Introduction: Type 4 familial partial lipodystrophic syndrome (FPLD4) is an autosomal dominant disease due to frameshift variants of PLIN1 gene. This gene encodes perilipin 1, a protein playing a key role in the structure of the adipocyte lipid droplet and in the regulation of lipolysis. Only 6 independent families with FPLD4 have been described. The aim of this work was to identify the major signs of the disease in the largest cohort of FPLD4 patients reported to date. Patients and Methods: Clinical and biological phenotype of 11 new patients with a family history of lipodystrophic syndrome and bearing a frameshift variant of PLIN1 gene, were investigated after written informed consent. Histological examination, and perilipin 1 protein expression analyses by western blot on whole cell extracts were performed on biopsies of adipose tissue in 2 patients. Results: We identified 3 heterozygous frameshift variants of PLIN1, segregating with the disease in 11 patients from 5 independent families. Our team had already described the p.Val398Glyfs*167 variant, and 2 new variants p.Gly362Glyfs*63 and p.Pro403Argfs*164 were identified. In all patients next generation sequencing (NGS) excluded any other molecular defect known to be responsible for lipodystrophy. On the studied adipose tissue samples, the PLIN1 variant leads to an abnormal longer form of perilipin 1 with fat fibrosis. The main signs of FPLD4 associate a partial, but also sometimes generalized lipoatrophy of post-pubertal occurrence and a phenotype of variable severity including muscular hypertrophy, acromegaloid facies, hirsutism, and metabolic complications (hypertriglyceridemia, insulin-resistance, diabetes, liver steatosis). Lipoatrophy might be missing or difficult to identify in men and youth. Leptin level was low or inappropriate to BMI, which was below 30 but not always very low. Conclusion: The clinical phenotype of FPLD4 is quite homogeneous, but the clinical diagnosis requires a careful clinical examination and/or an expert advice. An early genetic diagnosis is recommended to confirm the disease and prevent metabolic complications.